PEMANFAATAN ARANG KAYU GELAM SEBAGAI ADSORBEN UNTUK MENINGKATKAN KUALITAS AIR LIMBAH ZAT WARNA KAIN JUMPUTAN DI SENTRA INDUSTRI KAMPUNG KAIN KELURAHAN TUAN KENTANG KECAMATAN SEBERANG ULU 1 KERTAPATI KOTA PALEMBANG - Lisa Nopilda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Research has been carried out on the use of Gelam Wood Charcoal as an Adsorbent to Improve the Quality of Woven Dyestuffs in the Center of Industrial Village of Kelurahan Tuan Kentang, Seberang Ulu District 1 Kertapati, Palembang City with a combination treatment of contact time variations of 1 hour to 3 hours and activation time of charcoal with drying in the sun between 2 hours to 4 hours shows a significant effect on the quality of wastewater to be good. Temperatures from 32.3 oC dropped to 29.2 oC. The pH of wastewater from 6.1 to 6.9 is close to neutral pH 7. Soluble solids (TDS) drop from 483 ppm to 417 ppm and dissolved ions (EC) in wastewater drop from 1011 mS to 945.7 mS. Effectiveness of wood charcoal adsorbent in absorbing ions in waste with a combination combination of variations in contact time between 1 hour to 3 hours and activation time of charcoal with drying in the sun between 2 hours to 4 hours shows the optimum value in combination T3A1 ie at contact time 3 hour and 1 hour char activation time.